2016
DOI: 10.1155/2016/1835684
|View full text |Cite
|
Sign up to set email alerts
|

DUOX2 Expression Is Increased in Barrett Esophagus and Cancerous Tissues of Stomach and Colon

Abstract: Aim. To detect the expression of dual oxidase (DUOX) 2 in Barrett esophagus, gastric cancer, and colorectal cancer (CRC). Materials and Methods. The endoscopic biopsies were collected from patients with Barrett esophagus, while the curative resection tissues were obtained from patients with gastric cancer, CRC, or hepatic carcinoma. The DUOX2 protein and mRNA levels were detected with immunohistochemistry (IHC) and real-time quantitative PCR (qPCR). The correlation of DUOX2 expression with clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
14
1
Order By: Relevance
“…By immunohistochemistry, overexpression of DUOX2 was observed in the majority of colon cancers (62%), breast cancers (66%), non-small cell lung cancers (86%) and prostate cancers (92%) 15 . In a later study, both mRNA and protein levels of DUOX2 revealed significant up-regulation in gastric and colorectal cancers compared with adjacent normal tissue (all P ≤ 0.01) 16 . High expression of DUOX2 was also an independent prognosticator predicting both lower recurrent-free and overall survival rates in patients with hepatocellular carcinoma after hepatectomy 17 .…”
Section: Discussionmentioning
confidence: 77%
“…By immunohistochemistry, overexpression of DUOX2 was observed in the majority of colon cancers (62%), breast cancers (66%), non-small cell lung cancers (86%) and prostate cancers (92%) 15 . In a later study, both mRNA and protein levels of DUOX2 revealed significant up-regulation in gastric and colorectal cancers compared with adjacent normal tissue (all P ≤ 0.01) 16 . High expression of DUOX2 was also an independent prognosticator predicting both lower recurrent-free and overall survival rates in patients with hepatocellular carcinoma after hepatectomy 17 .…”
Section: Discussionmentioning
confidence: 77%
“…Overexpression of DUOX2/DUOXA2 during ulcerative colitis is thought to be responsible for oxidative DNA damage as a predisposing factor for development of colon cancer (MacFie et al ., ). Indeed, DUOX2 is often overexpressed in cancers of the alimentary tract, including colorectal cancers, and may contribute to cancer progression (Wu et al ., ; Qi et al ., ), suggesting that pharmacological inhibitors with selectivity towards DUOX2 may have clinical utility in anticancer treatment (Lu et al ., ). Recent studies also indicated a potential contribution of DUOX1 in promoting oxidative DNA damage and genomic instability in the thyroid in response to ionizing radiation, as a potentially important contributing feature to thyroid cancer (Ameziane‐El‐Hassani et al ., ).…”
Section: Duox In Disease Pathologymentioning
confidence: 99%
“…These mucosal surface cell types typically express high levels of unique NOX isoforms, the dual oxidases DUOX1 and/or DUOX2. Analogous to other NOXes, several studies have highlighted that DUOX2 mRNA and protein is often overexpressed in colorectal cancers[105, 106], pancreatic adenocarcinoma [107, 108], Barrett esophagus [105], and gastric cancers[105]. Using a newly developed monoclonal antibody against DUOX2, increased immunohistochemical staining was observed in various tumor types, including prostate, lung, breast, and colon [109].…”
Section: Specific Roles For Duox1 and 2 In Epithelial Cancersmentioning
confidence: 99%